Antimicrobial active herbal compounds against Acinetobacter baumannii and other pathogens - Tiwari, Vishvanath; Roy, Ranita; Tiwari, Monalisa (Frontiers in Microbiology, 2015)
Bacterial pathogens cause a number of lethal diseases. Opportunistic bacterial pathogens grouped into ESKAPE pathogens that are linked to the high degree of morbidity, mortality and increased costs as described by Infectious Disease Society of America. Acinetobacter baumannii is one of the ESKAPE pathogens which cause respiratory infection, pneumonia and urinary tract infections. The prevalence of this pathogen increases gradually in the clinical setup where it can grow on artificial surfaces, utilize ethanol as a carbon source and resists desiccation. Carbapenems, a β-lactam, are the most commonly prescribed drugs against A. baumannii. The high level of acquired and intrinsic carbapenem resistance mechanisms acquired by these bacteria makes their eradication difficult. The pharmaceutical industry has no solution to this problem. Hence, it is an urgent requirement to find a suitable alternative to carbapenem, a commonly prescribed drug for Acinetobacter infection. In order to do this, here we have made an effort to review the active compounds of plants that have potent antibacterial activity against many bacteria including carbapenem resistant strain of A. baumannii. We have also briefly highlighted the separation and identification methods used for these active compounds. This review will help researchers involved in the screening of herbal active compounds that might act as a replacement for carbapenem.